Oral Memoirs of Hoyt Smith - Smith, Hoyt (My University, 2016)
An oral history interview with Hoyt Smith, former director of Medical Graphics at the Tulsa Medical College.
Keywords: University of Oklahoma. Tulsa Medical College -- History.; Smith, Hoyt -- Interviews.; Medical illustrators -- Interviews.; Smith, Hoyt -- Career in medical illustration.; Medical education -- Oklahoma -- History.; Medical colleges -- Oklahoma -- History.; Medical illustration.